Advanced Mobile Communications - Jung, Peter (Germany : Degruyter, 2024)
This book is an extensively elaborated treatise on sophisticated channel coding for advanced mobile communications. Setting out from the author's own experience of university teaching for over three decades, the book covers the most fundamental aspects of sophisticated channel coding ranging for advanced mobile communications beginning with general concepts of information theory and number theory, block coding including cyclic and convolutional codes, important aspects of permutation matrices and Kronecker products and Reed-Muller codes, over convolutional turbo codes and low density parity check (LDPC) codes to polar codes.
Includes bibliography and index.
Keywords: Channel coding; Polar codes; Cyclic codes; 9